Hemangioblastoma in the setting of Von Hippel Lindau disease: a case report - Raajini Devi K.; Aida Zairani Mohd Zahidin; Hazlita Mohd Isa; Jemaima Che Hamzah; Farizal Fadzil; Safinaz Mohd Khialdin (Faculty of Medicine, UKM Medical Centre, 2016)
A 21-year-old Chinese gentleman with no known medical illness, presented with a history of right painless blurring of vision with central scotoma of two weeks duration. He also had a history of multiple episodes of seizures prior to presentation. Visual acuity was 1/60 with unremarkable anterior segment findings and no relative afferent pupillary defect. Fundus examination of the right eye revealed dilated and tortuous retinal veins with multiple retinal capillary hemangiomas and sub retinal hard exudates at the macula with edema. A diagnosis of Von Hippel Lindau disease was made when a posterior fossa mass suggestive of hemangioblastoma with obstructive hydrocephalus was seen on computed tomography of the brain. Craniotomy with nodule excision was performed. The retinal capillary hemangiomas were treated with the combination of laser photocoagulation and intravitreal Ranibizumab injections. Visual acuity subsequently improved to 6/36.